TÜRKİYE'DE 2018 YILINDA UYGULAMAYA KONULAN FEN BİLGİSİ ÖĞRETMENLİĞİ LİSANS PROGRAMININ 1998 ve 2006 LİSANS PROGRAMLARI İLE KARŞILAŞTIRILMASI. - ARDUÇ, Mehmet Akif; TAŞKIN, Gökhan; MUTLU, Fatma (Mehmet Akif Ersoy University Journal of Education Faculty, 2020)
The purpose of this study was to analyze the science teaching undergraduate program, which was put into effect in Turkey in 2018. The program contains significant changes compared to previous programs, applied in the years 1998 and 2006, under 4 sub-themes as "Scientific Field Knowledge", "Professional Teaching Knowledge", "General Culture", and "Elective Courses". The study was conducted using the document analysis method, which is among qualitative research methods. The science teaching undergraduate programs prepared by the Higher Education Council in 2018, 2006 and 1998, were analyzed via the descriptive analysis technique. As a result of the study, it was determined that there were differences between the undergraduate program of 2018 and the undergraduate programs of the years 1998 and 2006, in terms of the titles, hours, terms and numbers of "Scientific Field Knowledge", "Professional Teaching Knowledge", "General Culture" and "Elective Courses". In the current program, it was seen that theoretical course hours of field education were reduced; whereas, applied course hours remained the same. Theoretical course hours of professional knowledge were increased; whereas, applied course hours were reduced. The greatest change in terms of course numbers was observed in the field of professional knowledge with 11 courses in 1998; 13 courses in 2006; and 22 courses in 2018. Additionally, the courses which were not available in other programs were added to the current program and an increase was determined in the rate of elective courses and variety of courses. It was seen that School Experience course forming a step to the teaching application in the current program, was omitted from the program. On the other hand, as a result of the study, the programs were examined comparatively and suggestions were made by revealing positive and negative aspects of the new program.